Areas of application of nanotechnologies in animal husbandry - Boltianska, Natalia; Болтянська, Наталя Іванівна; Болтянская, Наталья Ивановна; Manita, Ihor; Маніта, Ігор Юрійович; Манита, Игорь Юрьевич; Podashevskaya, Н. (ТДАТУ, 2020)
Nanotechnologies - methods of nanoparticle management, as a result of which new methods of processing, manufacturing, state change, properties, shape of raw materials, materials or semi-finished products are developed.
Keywords: сompetitiveness; innovative technologies; nanotechnologies